Small mercies : a novel - Lehane, Dennis (New York, NY : Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
"One night Mary Pat's teenage daughter Jules stays out late and doesn't come home. That same evening, a young Black man is found dead, struck by a subway train under mysterious circumstances. The two events seem unconnected. But Mary Pat, propelled by a desperate search for her missing daughter, begins turning over stones best left untouched--asking questions that bother Marty Butler, chieftain of the Irish mob, and the men who work for him, men who don't take kindly to any threat to their business"--
Keywords: Missing persons -- Fiction; Irish Americans -- Fiction; Organized crime -- Fiction; Boston (Mass.) -- Fiction; Large type books; Thrillers (Fiction); Novels; Large print books